Development of a transformation model to derive general population–based utility: Mapping the pruritus–visual analog scale (VAS) to the EQ‐5D utility. Issue 4 (14th February 2017) - Park, Sun‐Young; Park, Eun‐Ja; Suh, Hae Sun; Ha, Dongmun; Lee, Eui‐Kyung
Abstract: Rationale, aims, and objectives: Although nonpreference‐based disease‐specific measures are widely used in clinical studies, they cannot generate utilities for economic evaluation. A solution to this problem is to estimate utilities from disease‐specific instruments using the mapping function. This study aimed to develop a transformation model for mapping the pruritus–visual analog scale (VAS) to the EuroQol 5‐Dimension 3‐Level (EQ‐5D‐3L) utility index in pruritus. Methods: A cross‐sectional survey was conducted with a sample (n = 268) drawn from the general population of South Korea. Data were randomly divided into 2 groups, one for estimating and the other for validating mapping models. To select the best model, we developed and compared 3 separate models using demographic information and the pruritus‐VAS as independent variables. The predictive performance was assessed using the mean absolute deviation and root mean square error in a separate dataset. Results: Among the 3 models, model 2 using age, age squared, sex, and the pruritus‐VAS as independent variables had the best performance based on the goodness of fit and model simplicity, with a log likelihood of 187.13. The 3 models had similar precision errors based on mean absolute deviation and root mean square error in the validation dataset. No statistically significant difference was observed between the mean observed and predicted values in all models. Conclusions: In conclusion, model 2 was chosen as the preferred mapping model. Outcomes measured as the pruritus‐VAS can be transformed into the EQ‐5D‐3L utility index using this mapping model, which makes an economic evaluation possible when only pruritus‐VAS data are available.